Cerita Rakyat, Identitas Naratif dan Katekese Umat - Dominicus Waso (Jurnal Alternatif Wacana Ilmiah Interkultural, 2012)
The core claim of this article is that oral traditions form the basis for which local people both trace their origins and at the same time endeavour to conceptualize their relationships with their fellow human beings and with the cosmos. It means that oral traditions are a fundamental tool for people in establishing their roots of life within a community and in assiting their efforts to establish authority within a society.the people narate their identity and this uniqueness is claimed not by exclusion but by relation to the others. What has been written here is a presentation about the genre of oral traditions in conjuction with an analysis about the church's prophetic role in teaching using the functional equivalence of the oral traditions.an important point to be emphasized in this article is that idiom, methaporand simile are fundamental to the styles ofspeech ofthe people are often used not just to explain something in more detail but also to trace the origins of an individual and conceptions oflife. It is for sure the oral tradition is a meditation on humanity.